Kolaborasi Pentahelix dalam Upaya Pengurangan Risiko Bencana pada Destinasi Wisata Di Desa Kalanganyar Sidoarjo - Mochammad Arfani (Jurnal Syntax Transformation, 2022)
The success of the development of the tourism sector can not be separated from synergistic collaboration from various parties. Synchronization of various tourism sectors is the basic capital for the achievement of tourism development. Regulation of the Minister (Permen) of Tourism of the Republic of Indonesia Number 14 of 2016 concerning the Guidelines for Sustainable Tourism Destinations states that in order for tourism to provide benefits and benefits to the community and its environment, there needs to be interconnection of systems, subsystems, sectors, and dimensions so as to create optimally integrated orchestration both the role of Bussiness, Government, Community, Academic, and Media (BGCAM) known as penta helix concept. The purpose of this research was to reduce the risk of disasters in tourist destinations in The Village of Kalanganyar Sidoarjo. From the results of discussions and supporting data in The Village of Kalanganyar Sedati District of Sidoarjo Regency, that pentahelix collaboration in reducing disaster risk in tourist destinations both for village tourism in Kapupaten Sidorjo including moderate category disaster prone areas according to data from the Indonesian Disaster Risk Index in 2020, such as natural disasters and non-natural disasters that occur. The Sidoarjo Regional Disaster Management Agency has a function and duties in handling disaster problems in Sidoarjo Regency, by making plans and programs for disaster prevention through disaster mitigation both pre-disaster, disaster and post-disaster. Pentahelix elements in Sidoarjo Regency participate in disaster management by collaborating and synergizing in disaster management such as from government elements, academic elements, business elements, community elements and mass media elements. By collaborating pentahelix, the community obtains knowledge about disasters and how to reduce the risk of disasters that occur so that the community has a preventive picture of disasters